Does development aid increase military expenditure? - Sarah Langlotz; Niklas Potrafke (University of Heidelberg, Department of Economics, 2016)
The diversion of development aid to the recipient's military may be one explanation why aid is often found to be ineffective in promoting economic growth and development. Previous studies have not derived the causal effects of development aid on military expenditure. Using a new instrumental variable strategy, we examine whether bilateral development aid increases military expenditure in recipient countries. The instrument is the interaction of donor government fractionalization and the probability of receiving aid. The dataset includes new data on military expenditure for 124 recipient countries over the 1975-2012 period. While development aid has a positive effect on military expenditure in the full sample, the effect vanishes when we exclude outliers. However, we find that aid provided by coordinated market economies increases military expenditure in the full sample of recipient countries, even after controlling for outliers. Coordinated market economies have been found to deliver more government-to-government aid, which has a higher risk of capture compared to aid delivered through non-state development actors.
urn:nbn:de:bsz:16-heidok-218765
Keywords: 330; aid; military expenditure; fungibility; instrumental variables; causality